REVIEW ON PELLETIZATION: DRY POWDER LAYERING OF PELLETS USING TANGENTIAL SPRAY ROTOR PROCESSOR/INSERT - RITIK R RAMDHANI; SURAJ C BHATT; PURNIMA D AMIN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Pelletization turns fine powders or granules into small, round pellets for easy flow and handling. These pellets offer advantages such as improved absorption, modified drug release patterns & reduced irritation at application sites. Dry powder layering is gaining popularity in the pharmaceutical industry due to its cost and time efficiency. This method is an effective and straightforward process, can be alternative to liquid-based coating techniques. In recent years, active pharmaceutical ingredient layering onto multi-particulate core materials. One innovative pelletization method uses a rotor processor for powder layering. This process involves applying drug powder onto sugar spheres & spraying a binder solution to achieve uniform distribution and enhance drying efficiency. Compared to traditional methods, this dry powder layering is faster & more energy-efficient, reducing drying time & energy consumption. It is a streamlined and eco-friendly method as no solvent is required which makes it beneficial for pellet coating. This article provide insights on the powder layering technique with innovative fluid bed pelletizing technologies like rotor processor, glatt powder coater granulator series, tangential spray in the rotary insert, complex perfect sphere insert and glatt procell series & their applications.